Comparison of 5-year outcomes and quality of life between endovenous laser (980 nm) and microwave ablation combined with high ligation for varicose veins - Fan, Pengcheng; Cong, Longlong; Dong, Jian; Han, Yang; Yang, Lin (Frontiers in Surgery, 2022)
Our study aims to evaluateand compare the long-term results of endovenous laser (EVLA) and microwave ablation (EMA) combined with high ligation in treating varicose veins (VVs).A total of 122 patients (150 legs) underwent EMA combined with high ligation, and 127 patients (167 legs) underwent EVLA procedures (980nm) combined with high ligation in this retrospective study. Outcomes included the Aberdeen Varicose Vein Questionnaire (AVVQ) score, the Venous Clinical Severity Score (VCSS), clinical recurrence of VVs and patient satisfaction duringthe 5-year follow-up.During the 5-year follow-up, patients who underwent the EVLA procedure showed a higher recurrence of VVs than those who underwent the EMA procedure (22.75% vs. 13.33%, P=0.03, odds ratio (OR): 1.91, 95% confidence interval (CI): 1.06-3.45), especially at the primary site (6% vs. 14.37%, P=0.01; OR, 2.63; 95% CI, 1.21-5.72). VV recurrence within 3 years was higher in patients who underwent EVLA than in those who underwent the EMA procedure (73.68% vs. 40%, P=0.01; OR, 4.2; 95% CI, 1.37-12.86). Compared with those at baseline, the AVVQ score, VCSS and EQ-5D score improved significantly at 5 years for patients who underwent either procedure (P<0.01); however, the VCSS and AVVQ score were higher for patients who underwent the EVLA procedure (P=0.05). The patient reintervention rate was higher for EVLA than for EMA (14.79% vs. 7.33%, P=0.033; OR, 2.19; 95% CI, 2.06-5.34). Our results confirmed that EMA and EVLA improve the QoL of patients and that EMA combined with high ligation demonstrates lower 5-year recurrence, especially at primary sites.